Reconstruction of Higher Education Curriculum to Prepare the Next Generations - Sarwanto Sarwanto (Proceeding of International Conference on Islamic Education, 2016)
Republic of Indonesia Government had issued a regulation on the national standards of higher education in 2015. UNS should immediately adjust the education process in accordance with the new regulations by reconstructing the curriculum. This study aims to analyze the reconstruction process in preparing the curriculum in UNS prepare future generations better. National standards require the higher education curriculum compiled from formulating learning outcomes to the preparation of the assessment system. This research method is a survey method. Samples are Diploma Program, Bachelor, Master Program, and Doctorate Program. Results showed that the reconstruction of the new curriculum is implemented by 45% of study program at the UNS, 60% of which is in conformity with the standards, even two courses had prepared the curriculum to standards well adapted to the AUN QA, only three study programs that have student learning outcomes have been agreed by the forum study program.